1913 N.C. Sess. Laws 57 - (:unkn) unknown (My University, 1913)
Pub. Laws, ch. 32 § 1: That any person being the parent or guardian of, or standing in loco parentis to, any child under the age of twelve years who shall knowingly permit such child to have the possession or custody of, or use in any manner whatever, any gun, pistol, or other dangerous firearm, whether such firearm be loaded or unloaded, or any other person, who shall knowingly furnish such child any such firearm, shall be guilty of a misdemeanor, and upon conviction shall be fined not exceeding fifty dollars, or imprisoned not exceeding thirty days.
Keywords: TRANSFER - MINORS